2014
DOI: 10.1007/s10815-014-0209-0
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of varicocelectomy on sperm proteins expression in patients with varicocele and poor sperm quality by using two-dimensional gel electrophoresis

Abstract: Purpose To compare proteomic profiles of spermatozoa from patients with varicocele and poor sperm quality before and after varicocelectomy. Methods This work was designed as a prospective and observational study. The study was based on 20 men with varicocele grade 3 and poor sperm quality undergoing varicocelectomy at the Fertility Unit of Royan institute in 2009. Two semen samples were collected, one before varicocelectomy and the other after surgery. Protein separation was done by two-dimensional protein ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 22 publications
2
27
1
Order By: Relevance
“…It has been shown a relationship between human sperm DNA damage and some semen parameters including concentration, morphology, and motility (Irvine et al, 2000;Lachaud et al, 2004;Henkel et al, 2010;Hosseinifar et al, 2013aHosseinifar et al, , 2014, whereas other studies did not demonstrate such association (Hughes et al, 1996;Henkel et al, 2003;Hosseinifar et al, 2013b). In this study, we also do not detect any significant correlation between DFI and sperm parameters in globozoospermic patients.…”
Section: Discussioncontrasting
confidence: 74%
“…It has been shown a relationship between human sperm DNA damage and some semen parameters including concentration, morphology, and motility (Irvine et al, 2000;Lachaud et al, 2004;Henkel et al, 2010;Hosseinifar et al, 2013aHosseinifar et al, , 2014, whereas other studies did not demonstrate such association (Hughes et al, 1996;Henkel et al, 2003;Hosseinifar et al, 2013b). In this study, we also do not detect any significant correlation between DFI and sperm parameters in globozoospermic patients.…”
Section: Discussioncontrasting
confidence: 74%
“…The significant decreased SOD1, GSH and CAT levels in seminal plasma of infertile men complaining of varicocele was in agreement with previous study that showed significantly reduced levels of enzymatic antioxidants in the semen of infertile men with varicocele [22]. The level of GSH, SOD1 and CAT had significant increase in varicoceloctomized group compared to varicocele group which in agreement with Hosseinifar et al [23] whom identified SOD1 significantly lower in samples before varicocelectomy compared with after surgery. These proteins are essential for normal sperm production and are affected by the heat generated by the existence of a varicocele.…”
Section: Resultssupporting
confidence: 91%
“…; Hosseinifar et al . ). The DSCAML1 gene, 6 Mb away from the significant SNP BTA‐123344‐no‐rs , was found to increase the occurrence of sperm head defects and to be associated with poor sperm morphology, sperm production and the male reproductive process (Kosova et al .…”
Section: Descriptive Statistics Of the Deregressed And Original Estimmentioning
confidence: 97%